Pengolahan Ikan Tuna menjadi Sambal Ikan Tuna (Sauna) Sebagai Produk Bernilai Jual Tinggi di Desa Sukaraja, Kabupaten Sukabumi, Jawa Barat - Djoko Poernomo; Pika Rahmadhiani (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Pertanian Bogor, 2019)
Tuna chilli is a new innovation product made from tuna and the first was produced by IGTF Sukabumi participants along with the Saluyu Group in Sukaraja Village, Sukabumi Regency. The tuna sambal processing activity is not only for the Saluyu Group but also demonstrated by IGTF participants to the local community. The demonstration of tuna sauce processing (SAUNA) was carried out on Thursday, 9 August 2018 at 11.00-12.30 WIB at the Saluyu Group Production Room, Sukaraja Village, Sukabumi Regency. Demonstration activities processed by SAUNA products are the main activities carried out to provide knowledge on ways to increase fish consumption by creating various processed products at affordable prices and of good quality. Tuna is one of the important economical fish species in the world and is the third largest fishery in Indonesia after demersal shrimp and fish but has a higher selling price than other fishery commodities. Tuna fish processing can increase the sale value of the tuna itself and can encourage the growth of the fish processing industry so that it can improve the welfare and prosperity of the community. The tuna sambal product can be well received by local people who have carried out organoleptic test with parameters of taste, aroma, and color.